Microneedle-assisted microparticle delivery by gene guns: experiments and modeling on the effects of particle characteristics. (May 2015) - Zhang, Dongwei; Rielly, Chris D.; Das, Diganta B.
Abstract Microneedles (MNs) have been shown to enhance the penetration depths of microparticles delivered by gene gun. This study aims to investigate the penetration of model microparticle materials, namely, tungsten (<1 μm diameter) and stainless steel (18 and 30 μm diameters) into a skin mimicking agarose gel to determine the effects of particle characteristics (mainly particle size). A number of experiments have been processed to analyze the passage percentage and the penetration depth of these microparticles in relation to the operating pressures and MN lengths. A comparison between the stainless steel and tungsten microparticles has been discussed, e.g. passage percentage, penetration depth. The passage percentage of tungsten microparticles is found to be less than the stainless steel. It is worth mentioning that the tungsten microparticles present unfavourable results which show that they cannot penetrate into the skin mimicking agarose gel without the help of MN due to insufficient momentum due to the smaller particle size. This condition does not occur for stainless steel microparticles. In order to further understand the penetration of the microparticles, a mathematical model has been built based on the experimental set up. The penetration depth of the microparticles is analyzed in relation to the size, operating pressure and MN length for conditions that cannot be obtained in the experiments. In addition, the penetration depth difference between stainless steel and tungsten microparticles is studied using the developed model to further understand the effect of an increased particle density and size on the penetration depth.